Performance based discrete topology optimization of steel braced frames by a new metaheuristic. (September 2018) - Gholizadeh, Saeed; Ebadijalal, Mehrdad
Highlights: A unique framework for discrete topology optimization of steel braced-frames (SBFs) is presented. Topology optimization and performance-based design are integrated. Seismic performance is checked using nonlinear pushover analysis results. A new metaheuristic is proposed, center of mass optimization (CMO). CMO outperforms other metaheuristics in seismic topology optimization of SBFs. Abstract: Seismic topology optimization of structures is a challenging field of structural engineering. So far, a little number of studies has been conducted on this regard and all of them have presented conceptual designs which are of limited practical applicability. The main aim of the present study is to find the practical optimal placement of X- and diagonal bracing systems in steel braced frames subject to seismic loading. To achieve this purpose, a discrete topology optimization formulation is proposed in the framework of seismic performance-based design. A new metaheuristic algorithm, center of mass optimization (CMO), is proposed to deal with the performance-based discrete topology optimization (PBDTO) problem based on the physical concept of center of mass for mass distribution in space. Two challenging benchmark structural optimization problems are presented in order to demonstrate the computational merit of the proposed CMO algorithm compared to a number of algorithms in literature. Furthermore, PBDTO process is implemented for four multi-story steel braced frames by CMO. Performance of the proposed CMO-based discrete topology optimization framework in finding practical topology of bracing members for SBFs is demonstrated on PBDTO examples.